Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1093/neuonc/noq148
|View full text |Cite
|
Sign up to set email alerts
|

A single intravenous injection of oncolytic picornavirus SVV-001 eliminates medulloblastomas in primary tumor-based orthotopic xenograft mouse models

Abstract: Difficulties of drug delivery across the blood-brain barrier (BBB) and failure to eliminate cancer stem cells (CSCs) are believed to be the major causes of tumor recurrences in children with medulloblastoma (MB). Seneca Valley virus-001 (SVV-001) is a naturally occurring oncolytic picornavirus that can be systemically administered. Here, we report its antitumor activities against MB cells in a panel of 10 primary tumor-based orthotopic xenograft mouse models. We found that SVV-001 killed the primary cultured x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
84
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 61 publications
(71 reference statements)
3
84
0
1
Order By: Relevance
“…These cancers constitute a major cause of morbidity and mortality -SCLC alone is responsible for approximately 30,000 deaths annually in the US (5). Previous studies in preclinical mouse models and early-phase clinical trials confirmed the safety and potential efficacy of SVV as a novel cancer treatment, but clinical development of SVV has been hampered by a lack of understanding of host dependency factors (2,3,(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…These cancers constitute a major cause of morbidity and mortality -SCLC alone is responsible for approximately 30,000 deaths annually in the US (5). Previous studies in preclinical mouse models and early-phase clinical trials confirmed the safety and potential efficacy of SVV as a novel cancer treatment, but clinical development of SVV has been hampered by a lack of understanding of host dependency factors (2,3,(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Adenovirus 16p and chimpanzee adenovirus CV23 have been shown to infect both CD133+ and CD133− primary glioma cells (Skog, Edlund et al 2007). Treatment with adenovirus Delta-24-Arg-Gly-Asp (RGD) (Jiang, Gomez-Manzano et al 2007), the naturally occurring picornavirus Seneca Valley virus-001 (Yu, Baxter et al 2011), or herpes simplex virus (HSV) vector G47Δ (Wakimoto, Kesari et al 2009) effectively killed BTSCs and significantly improved survival in mice bearing BTSC xenografts. Combining HSV vector G47Δ with temozolomide increased sensitivity to temozolomide in killing BTSCs while sparing neurons and induced long-term remission in 4 of 8 treated xenograft-bearing mice (Kanai, Rabkin et al 2012).…”
Section: Oncolytic Viral Approaches For Targeting Btscsmentioning
confidence: 99%
“…114,115 Since its introduction as an oncolytic virus in 2007, SVV has shown preclinical efficacy in nude mice xenograft models for several malignancies. [114][115][116][117][118] In a phase I clinical trial employing an intravenous dose escalation in patients with neuroendocrine tumors, SVV had (marginal) treatment benefits without causing serious adverse events when administered even in high dose (10 11 viral particles/kg). 119 A phase II RCT in patients with extensive stage NSCLC and a phase I dose escalation trial in pediatric patients with neuroblastoma, rhabdomyosarcoma or rare tumors with neuroendocrine features are currently underway.…”
Section: Family Picornaviridae: Seneca Valley Virus (Svv)mentioning
confidence: 99%